Study on the activity of some enzymes concerned with pyrethroids metabolism in subterranean termite (Reticulitermes chinensis Snyder) - TAN Su-jin; HE Jun-hua; TAN Xiao-hong; DU Lin-fang; TANG Zhen-hua (浙江大学学报. 农业与生命科学版, 2000)
The activity of some important enzymes of Reticulitermes chinensis Snyder concerned with pyrethroid metabolism was studied in vitro. The results showed that the activity of CarEs and mfo in Reticulitermes chinensis Snyder was between those of the susceptible strains of Musca dornestica L. and Heliothis armigera Hübner. But the activity level of mfo was significantly lower than that of susceptible strains of housefly. So pyrethroids could be reasonably applied to controlling of Reticulitermes chinensis Snyder. Activity of Na-K-ATPase could not be detected on the synaptosome of Reticulitermes chinensis Snyder, but much higher activity of Ca-ATPase was determined on the same membrane at 2.16×106 (µmol/L·mg·min). The result implies that Ca-ATPase on the synaptosome of Reticulitermes chinensis Snyder may play a similar role of Na-K-ATPase as on the same place in other insects.